RELIGIUSITAS DIGITAL DAN DIMENSI PERLAWANAN MILENIAL DALAM RUANG ONLINE - Hanry Harlen Tapotubun; Hilda Rahmah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
This article aims to analyze the reasons behind the increasing number of expressing the religiosity on social media by the millennials, especially by discussing the preconditions those religious expressions. This study uses a qualitative approach with literature-based and netnographic study methods. It is also supported by interviews and observations on social media related to the activities of millennials in expressing their religiosity on Instagram, Facebook and WhatsApp. The results showed that the massive expression of religiosity on social media by the millennial could be considered as a